2011
DOI: 10.1089/lap.2010.0407
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Laparoscopic Approach for Anastomotic Leakage After Minimally Invasive Surgery for Colorectal Cancer

Abstract: Compared with conventional open treatment of anastomotic leakage, the laparoscopic approach resulted in fewer wound complications and tendency of early recovery of bowel movement without an increase in adverse outcomes. Using a laparoscopic approach, all the advantages of minimally invasive surgery can be realized in patients who develop anastomotic leakage after minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
0
24
0
3
Order By: Relevance
“…Two studies reported statistically significant differences in ASA grades among the patients. In the study reported by Kwak and colleagues, there was a significant difference in the proportion of patients with a high ASA grade; six patients in the OR group ( versus 0 of 26 in the laparoscopic group) had a high ASA grade owing to their acute presentation ( P = 0·027). Vennix and colleagues included a higher proportion of patients with an ASA grade of III–IV who had OR than LR (24·3 versus 17·0 per cent; P = 0·048).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Two studies reported statistically significant differences in ASA grades among the patients. In the study reported by Kwak and colleagues, there was a significant difference in the proportion of patients with a high ASA grade; six patients in the OR group ( versus 0 of 26 in the laparoscopic group) had a high ASA grade owing to their acute presentation ( P = 0·027). Vennix and colleagues included a higher proportion of patients with an ASA grade of III–IV who had OR than LR (24·3 versus 17·0 per cent; P = 0·048).…”
Section: Resultsmentioning
confidence: 86%
“…The rate of second reoperation in the comparative studies ranged from 0 to 12 and 0 to 28 per cent in the LR and OR groups respectively. The study with the highest secondary reoperation rate (12 per cent) following LR also had a high proportion of patients who required repeat reoperations in the open group (19 per cent).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations